Evaluation of Liquefaction Hazard in the West Coastal Area of Bengkulu City Due to Megathrust Earthquake - Valetta, Fitria Leonni; Mase, Lindung Zalbuin; Amri, Khairul; Misliniyati, Rena; Hardiansyah, Hardiansyah (JPFT (Jurnal Pendidikan Fisika dan Teknologi) (Online), 2025)
This study analyzes the liquefaction potential in the coastal area of Bengkulu due to the large subduction earthquake in 2007. The study was conducted systematically, beginning with field investigations with shear wave velocity measurements. Spectral matching and ground motion prediction based on relative attenuation models were conducted to obtain a representative picture of ground motion at the study site. Subsequently, soil response analysis was used to evaluate the behaviour of the soil under seismic loading. A non-linear finite element approach was applied to assess the dynamic characteristics of the soil, including excess pore water pressure, shear stress-strain response, and stress path. In addition, an empirical evaluation was conducted to determine the liquefaction potential. The results show that liquefaction has the potential to occur at shallow depths, especially in the first and second layers of the sand layer. The results of numerical and empirical analyses show consistent patterns and agreement. The comparison between the excess pore pressure ratio and the safety factor aligns with the findings from previous studies. These findings emphasise the importance of implementing seismic hazard mitigation measures in the study area.